MENGUKUR KINERJA PEGAWAI MELALUI PROSEDUR LAYANAN E-KTP DI KANTOR CAMAT PONTIANAK KOTA - Ganda Sahata Sembiring E.01107042 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
E-KTP-making procedures in the District of Pontianak city is done by the applicant with a letter of introduction from the RT and subsequently in the village and in the District through the Head of Government. For applicants already have a National Identity Card SIAK, Petitioner SIAK just bring valid ID to be processed into E-KTP in the district to do the recording identity with the recording procedure facial photos, signature recording, recording fingerprints and iris recording. Factors causing the length of the process of making Electronic Identity Card (e-ID) in the district of Pontianak are internal factors that caused Limitations of Human Resources at District of Pontianak City Employees who understand IT problems because of the recording process using a specially designed computer that contains the specific application and its new are less understood by the employee in carrying out the recording process, and the external factors that pertain to the tool E-KTP and its application, network and place the E-ID card issuance. Performance Services E-KTP in Sub Pontianak city already meet the standards of efficiency, effectiveness, fairness, and responsiveness desired in accordance with existing procedures, in performing the service has a maximum on the pattern of performance of employees in providing services to the public Keywords: Performance measurement of e-ID card, the applicant registration, recording, publishing e-ID card